Empty Nest Syndrome - An Obstacle for Alcohol Abstinence - Shakya, DR (Journal of Nepal Health Research Council, 2010)
Empty nest syndrome is a general feeling of loneliness, sadness, and/ or grief that parents/ other guardian relatives may feel when their children leave home. This condition, more prevalent in women, is more common in modern times probably because extended family is becoming uncommon and the elderly are more left living by themselves. Current day Nepal is no more exception. We report a case of 'alcohol dependence' with 'empty nest syndrome' of a 49-year-old lady presented with 4-year history of episodic depression and increased drinking. She had been drinking for 10 years and more for last 4 years. This case report highlights importance of family support and of addressing co-morbid psychiatric disorder for effective management of alcohol problem. Key words: alcohol; alcohol dependence; depression; empty nest syndrome; psychiatric co-morbidity.   DOI: 10.3126/jnhrc.v7i2.3023 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 135-137